2014
DOI: 10.1080/10590501.2014.967053
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Cancers in Serbia and Possible Connection with Cyanobacterial Blooms

Abstract: Cyanobacteria produce toxic metabolites known as cyanotoxins. These bioactive compounds can cause acute poisoning, and some of them may promote cancer through chronic exposure. Direct ingestion of and contact with contaminated water is one of the many exposure routes to cyanotoxins. The aim of this article was to review the incidence of 13 cancers during a 10-year period in Serbia and to assess whether there is a correlation between the cancer incidences and cyanobacterial bloom occurrence in reservoirs for dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 66 publications
1
29
1
1
Order By: Relevance
“…MCs) from drinking water could present a risk factor for primary liver cancer and possibly even other types of cancer (Svirčev et al, 2010;Drobac, 2015). Epidemiological studies conducted in Serbia have revealed a significant correlation between an increased incidence of several cancers (brain; heart, mediastinum and pleural; ovarian; testicular; gastric; colorectal; retroperitoneal and peritoneal; leukemia; malignant skin melanoma; and primary liver cancer) and cyanobacterial blooms in reservoirs used for drinking water supply (Svirčev et al, 2009(Svirčev et al, , 2013b(Svirčev et al, , 2014bDrobac, et al 2011;Drobac, 2015).…”
Section: Reservoirs Used For Drinking Water Supplymentioning
confidence: 99%
“…MCs) from drinking water could present a risk factor for primary liver cancer and possibly even other types of cancer (Svirčev et al, 2010;Drobac, 2015). Epidemiological studies conducted in Serbia have revealed a significant correlation between an increased incidence of several cancers (brain; heart, mediastinum and pleural; ovarian; testicular; gastric; colorectal; retroperitoneal and peritoneal; leukemia; malignant skin melanoma; and primary liver cancer) and cyanobacterial blooms in reservoirs used for drinking water supply (Svirčev et al, 2009(Svirčev et al, , 2013b(Svirčev et al, , 2014bDrobac, et al 2011;Drobac, 2015).…”
Section: Reservoirs Used For Drinking Water Supplymentioning
confidence: 99%
“…Recent reviews on human and animal health aspects include: a health review chapter (Codd et al, 2017), an epidemiological assessment of cancers in Serbia with reference to cyanobacterial blooms (Svirčev et al, 2014a), a review of production, toxinology and toxicology of the ANTX-a and STX neurotoxins (Testai et al, 2016) and a review on epidemiological investigations on health issues related to cyanotoxins (Svirčev et al, 2017a). Recently reported animal intoxications involving cyanobacterial blooms and cyanotoxins have included dogs in the Netherlands, with hANTX-a (Faassen et al, 2012b) and MC-LR (Lürling and Faassen, 2013) as likely proximal causes.…”
Section: Fate Impact and Health Effectsmentioning
confidence: 99%
“…Their acute effetcs are primarily manifested in liver but MCs have been shown to induce gastrointestinal and renal damage or neurological symptoms as well (Manganelli et al, 2012). Chronic exposures to MCs have been linked to tumor promoting and carcinogenic effects which is based on laboratory animal and in vitro experiments (Svircev et al, 2010) and supported also by results of epidemiologic studies of human population consuming drinking water contaminated by these cyanotoxins (Fleming et al, 2002;Svircev et al, 2009Svircev et al, , 2013Svircev et al, , 2014Ueno et al, 1996;Yu et al, 1995;Zhou et al, 2002). In fact, MCs have been classified as possible human carcinogen (class 2B) by the International Agency for Research on Cancer (Grosse et al, ).…”
Section: Introductionmentioning
confidence: 70%
“…Chronic exposures to water contaminated with MCs at concentrations 1.1-3.28 µg L -1 have been linked with the increased incidence of colorectal cancer (Zhou et al 2002) or liver damage (Chen et al, 2009;Li et al, 2011) in China. In addition, there are reports on statistically significant associations between cyanobacterial blooms and non-alcoholic liver disease in USA (Zhang et al, 2015) or primary liver cancer in Serbia (Svircev et al, 2009(Svircev et al, , 2013(Svircev et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%